MAIN HAZARDS AND NEGATIVE IMPACT OF ENVIRONMENTAL FACTORS IN BIODIVERSITY CONSERVATION OF THE «KYRGYZ-ATA» NATIONAL NATURAL PARK (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article considers the current state of the biodiversity of the “Kyrgyz-Atinskiy” Natural National Park and the influence of environmental factors. A general description of the areas covered with forests is given and an analysis of the influence of environmental factors on the biological diversity of the park territory is carried out. The studies were carried out on specially allocated three sites, as a result, an assessment of the ecological state was given and measures were proposed to preserve the park’s ecosystem from the influence of various negative factors.